Single nucleotide polymorphisms may explain the contrasting phenotypes of two variants of a multidrug-resistant Mycobacterium tuberculosis strain - Bigi, María Mercedes (2017)
Fil: Bigi, María Mercedes. Universidad de Buenos Aires, Facultad de Agronomía, Cátedra de Microbiología Agrícola. INBA-CONICET, Av. San Martín 4453, C1417DSE, Buenos Aires; Argentina.